Acute stress modulates hippocampal to entorhinal cortex communication - Nasretdinov, Azat; Jappy, David; Vazetdinova, Alina; Valiullina-Rakhmatullina, Fliza; Rozov, Andrei (Frontiers in Cellular Neuroscience, 2023)
Feed-forward inhibition is vital in the transfer and processing of synaptic information within the hippocampal -entorhinal loop by controlling the strength and direction of excitation flow between different neuronal populations and individual neurons. While the cellular targets in the hippocampus that receive excitatory inputs from the entorhinal cortex have been well studied, and the role of feedforward inhibitory neurons has been attributed to neurogliafom cells, the cortical interneurons providing feed-forward control over receiving layer V in the entorhinal cortex remain unknown. We used sharp-wave ripple oscillations as a natural excitatory stimulus of the entorhinal cortex, driven by the hippocampus, to study the function of synaptic interactions between neurons in the deep layers of the entorhinal cortex. We discovered that CB1R-expressing interneurons in the deep layers of the entorhinal cortex constitute the major relay station that translates hippocampal excitation into efficient inhibition of cortical pyramidal cells. The impact of inhibition provided by these interneurons is under strong endocannabinoid control and can be drastically reduced either by enhanced activity of postsynaptic targets or by stress-induced elevation of cannabinoids.